Factors affecting use of fixed-route and demand-responsive services in a university community - Muhammad Arif Khan; Roya Etminani-Ghasrodashti; Apurva Pamidimukkala; Sharareh Kermanshachi; Jay Michael Rosenberger; Greg Hladik (Discover Cities)
Abstract Shared mobility systems are declining in university communities, despite its reputation as an economical, sustainable, and appealing alternative to private cars. Competition for the services is fierce, as potential users have a variety of transportation options, ranging from low-cost rides that organizations and employers offer their members and employees to inexpensive, or even free, transit services that universities offer their students, faculty, and staff. Determinant factors of ridership trends for shared mobility have been studied extensively; however, little attention has been paid to the ridership patterns of services available only to university students, faculty, and staff. This study attempts to bridge that gap by exploring that that how the university community uses specific services (modes including fixed route, and on-demand ridesharing), why some don’t avail themselves of some of the services, and the most critical factors associated with the frequency of students’ usage. To address the research questions, this study conducted an online survey of a university community in 2022 and collected travel data related to the use of four available fixed-route and demand-responsive services over six months. The results revealed that international students, males, and students without a personal vehicle in the household are most likely to use university-provided shared mobility systems, but the majority of them, are not aware of the services. Findings from this study will enable university transit planners to improve transit services so that they meet the student’s needs and reduce their reliance on private vehicles.